The introduction and development of reinforced concrete structures in modern Suzhou（1919–1933）: a case study of the Cline Hall at Soochow University - Xi Chen; Qinyi Shi; Shiruo Wang (Journal of Asian Architecture and Building Engineering)
The introduction of reinforced concrete structures to China occurred in the late 19th century via Shanghai and other cities. While Shanghai has been extensively researched in terms of its reinforced concrete structures, Suzhou, located near Shanghai and one of the early adopters of reinforced concrete construction, has received less attention. This study aims to investigate the impact of reinforced concrete structures in early modern Suzhou, focusing on Cline Hall as a case study, which stands one of Suzhou’s earliest buildings with a reinforced concrete structure. Drawing on the close relationship between Suzhou and Shanghai in terms of architectural design, construction technology and materials. The study examines the opportunities for the introduction, the types and layouts of reinforced concrete structure systems, and the forms of materials in modern Suzhou (1919–1933). Additionally, material testing was conducted to provide a preliminary assessment of the aggregate ratios and durability of the reinforced concrete. This paper offers a foundation and recommendations for the conservation of Cline Hall, as well as other modern reinforced concrete buildings in Suzhou. By shedding light on the lesser-explored aspect of reinforced concrete heritage in modern Suzhou, this paper contributes to the broader understanding of architectural history and conservation practices.